Serious illness conversations in pulmonary hypertension. (1st October 2021) - Ismail, Reem; Hegab, Sara; Kelly, Bryan; Franco‐Palacios, Domingo J.; Grafton, Gillian; Smith, Zachary R.; Awdish, Rana L.A.
Abstract : Pulmonary arterial hypertension has evolved from a fatal disease with few treatment options to a chronic condition with improved survival. This improvement is possible through development of effective therapies as well as the expansion of risk stratification scores to assist clinical decision making. Despite improved disease control, quality of life, and overall prognosis, many challenges remain. The treatment itself is burdensome, with significant impact on quality of life. Many patients with pulmonary arterial hypertension still present with advanced, often end‐stage disease. Increased use of mechanical circulatory support and catheter‐based interventions have expanded use of extracorporeal life support and right ventricle assist devices. For these reasons as well as the long‐term relationships pulmonary hypertension physicians have with patients and their families, navigating the course of the illness in a considered, proactive way is essential. Understanding individual goals and revisiting them as they change over time requires comfort with the conversation itself. There are many barriers and challenges to having effective, compassionate conversations in the clinical setting with time constraints being the most often cited. Compressed visits are necessarily focused on the clinical aspects, therapy and medication adherence and tolerance. Clinicians are sometimes wary of diminishing hope in the face of ongoing treatment. Having sufficient experience and comfort with these discussions can be empowering. In this paper, we discuss the challenges involved and propose a framework to assist in incorporating these discussions into clinical care.